2015
DOI: 10.1007/s00264-015-2941-1
|View full text |Cite
|
Sign up to set email alerts
|

A 21 % conversion rate to total knee arthroplasty of a first-generation patellofemoral prosthesis at a mean follow-up of 9.7 years

Abstract: A 21 % conversion rate to total knee arthroplasty of a first-generation patellofemoral prosthesis at a mean follow-up of 9.7 years (range, 110-200). Median VAS Pain was 30 (range, 0-80) and VAS Satisfaction median was 90 (range, 50-100). Thirteen (62 %) PFAs were rated excellent, six (28 %) as good and two (10 %) as fair. Twelve (36 %) of the cases required further surgery within 4 years after implantation. Seven of these (21 %) were converted to TKA after a mean time of 5.5 years, five out of seven were conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 22 publications
0
13
0
2
Order By: Relevance
“…This finding was explained by the fact that the anterior and distal femoral TKA cuts ultimately eliminated any residual bone defect following explanation of the trochlear component from the prior PFA. With respect to the patellar button from the previous PFA, several studies have demonstrated that either preservation or removal can be accomplished with minimal difficulty 37,91 . For instance, Lonner et al left the patellar button in place in all cases 37 , and van Jonbergen et al revised the button in all cases because the implant had a poor track record 81 .…”
Section: Conversion Tka After Prior Patellofemoral Arthroplasty (Pfa)mentioning
confidence: 99%
“…This finding was explained by the fact that the anterior and distal femoral TKA cuts ultimately eliminated any residual bone defect following explanation of the trochlear component from the prior PFA. With respect to the patellar button from the previous PFA, several studies have demonstrated that either preservation or removal can be accomplished with minimal difficulty 37,91 . For instance, Lonner et al left the patellar button in place in all cases 37 , and van Jonbergen et al revised the button in all cases because the implant had a poor track record 81 .…”
Section: Conversion Tka After Prior Patellofemoral Arthroplasty (Pfa)mentioning
confidence: 99%
“…36 % der Prothesen mussten sich 4 Jahre nach Implantation einem weiteren Eingriff unterziehen. Nach 5,5 Jahren wurden 21 % auf eine totalendoprothetische Versorgung konvertiert 35 . Die Daten der Endoprothesenregister zeigen jedoch auch, dass pro Chirurg nur wenige patellofemorale Prothesen implantiert werden.…”
Section: Ergebnisse Des Patellofemoralen Gelenkersatzesunclassified
“…Design limitations, such as narrow anterior femoral flange width and suboptimal trochlear implant geometry, led to patellar tracking problems, instability, subluxation, and impingement. Failure rates were reported between 17.8-44%, 20-33%, 10-42%, and 16-78%, in the Depuy's Autocentric™, Depuy's LCS™, Smith & Nephew's Richards™, and Waldemar's Lubinus™, respectively [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: History and Implant Modelsmentioning
confidence: 99%